EUS-Guided Pancreatic Cyst Brushing: A Comparative Study in a Tertiary Referral Centre - Thomas, Titus; Bebb, James; Mannath, Jayan; Ragunath, Krish; Kaye, Phillip V; Aithal, Guruprasad P (JOP. Journal of the Pancreas, 2010)
Context Fluid analysis obtained by EUS guided FNA is used to aid in diagnosis and management of cystic lesions in the pancreas. Complementing fluid aspiration with brushing of cyst wall may increase the cellular yield. Objective To compare cellular yield of pancreatic cyst FNA with and without wall brushing. Design Comparative study. Setting Tertiary referral centre. Patients Fifty-one patients with cystic pancreatic lesions referred for EUS-guided aspiration/sampling were included (median age 69 years; interquartile range: 49-77 years). Main outcome measures Comparing adequacy of cellular yield between EUS-guided aspiration alone vs. EUS-guided aspiration and cyst wall brushing. Intervention EUS-guided FNA and/or wall brushing (aspiration only: No. 27; brushing: No. 24). Results There was no significant difference in age (P=0.496) cyst size (P=0.084) or cyst location (P=0.227) between groups. Overall 29.5%; (15/51) of samples were acellular/insufficient with no significant difference between the two groups (22.2% in the aspiration only group vs. 37.5% in the brushing group; P=0.356). The remaining samples were adequate for cytological evaluation (77.8% vs. 62.5%; aspiration only vs. brushing groups). Seventeen cases were neoplastic (8 benign, 9 malignant). The diagnostic accuracy was 61.9% and 55.0% in aspiration only and brushing groups, respectively. Two out of 4 (50.0%) patents were diagnosed as having cancer in the brushings group compared to 1/5 (20.0%) in the FNA only group (P=0.524). Limitations Non-randomised series. Conclusions The cellular yield was similar in FNA and brushing group. Greater proportion of patients with malignant cystic pancreatic lesions diagnosed by EUS sampling was in the brushing group, but this did not reach statistical significance. Image: Linear endoscopic ultrasound showing EUS-guided brushing of a cystic pancreatic lesion.